PICMET '07 - 2007 Portland International Conference on Management of Engineering &Amp; Technology 2007
DOI: 10.1109/picmet.2007.4349592
|View full text |Cite
|
Sign up to set email alerts
|

Personality Composition, Affective Tie and Knowledge Sharing: A Team Level Analysis

Abstract: Since knowledge has became the most valuable asset for organizations in the knowledge-economy age, related issues of knowledge management have been getting more and more attention, especially the concept of knowledge sharing, because it is a necessary condition for organizations to perform fruitful knowledge transfer and creation, which will then help them gain and sustain competitive advantage. Previous research has for the most part only studied how to induce employees to perform knowledge sharing at the ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 50 publications
(59 reference statements)
0
13
0
Order By: Relevance
“…An increased level of knowledge sharing within groups indicates that members are more willing to engage in knowledge sharing with colleagues (Hsu et al, 2011). It is important to understand how to promote knowledge sharing at the group level.…”
Section: Introductionmentioning
confidence: 99%
“…An increased level of knowledge sharing within groups indicates that members are more willing to engage in knowledge sharing with colleagues (Hsu et al, 2011). It is important to understand how to promote knowledge sharing at the group level.…”
Section: Introductionmentioning
confidence: 99%
“…Studies' findings report that the mean level of Openness to experience in team compositions positively influences knowledge sharing among team members ( [14], [18]). It means that a team composed of higher aggregate levels of Openness to experience resulted into higher levels of knowledge sharing [14].…”
Section: Discussionmentioning
confidence: 99%
“…Studies' findings report that the mean level of Openness to experience in team compositions positively influences knowledge sharing among team members ( [14], [18]). It means that a team composed of higher aggregate levels of Openness to experience resulted into higher levels of knowledge sharing [14]. LePine [17] stated that "In a team setting, open individuals should not only make more suggestions, but because they tend to be insightful, enthusiastic, and talkative, they should tend to build on the ideas of other members" (p. 32).…”
Section: Discussionmentioning
confidence: 99%
“…They are more like to avoid CMC tools from their daily task. High extraversion people will be more involved in knowledge-sharing activities among individuals (Gupta, 2008;Hsu, Wu, & Yeh, 2007). Guptha and Govindarajan (2000) found that communication knowledge sharing is essential.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Extroverts are emotionally positive they are satisfied when they are working with the team. Within the group knowledge sharing will be increased and then can ensure that the team will remain viable (Hsu, Wu, and Yeh 2007). For example, extroverted university students share the library information with their team members to complete group assignments when completing it depends on a lot of online sources from the library website (Teh, Yong, Chong, & Yew, 2011).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%